Caracterização do uso e ocupação na orla da zona central de Belém: subsídio ao gerenciamento costeiro e proposição do cinema como ferramenta de acessibilidade - CELESTINO, Edmir Amanajás (2018)
Characterizes the current state of use and occupy of the central coast zone of Belém city, and aspects of the resident population and who frequents that place, conditioned directly or indirectly, by the implementation of public policies related to coastal management, to proposing a methodology incorporating the vision of the population about their relationship with the river, which can subsidize a comparative analysis between this and other areas of the waterfront of Belém, according to the hypothesis that the coast of the central zone is urbanized and its urbanization agree with the proposed land-use and occupancy as described in managing plan, in order to generate subsidies for local coastal management, aiming to characterize the specific purpose of using property situated on the coast of Belém and the central coast points of free access to waterfront, reviewing the implementation of the Urban Managing Plan (UMP) and support a film making of on the waterfront of the central area of Belém by proposing a documentary project. There are stages of occupation started at different times of the city growth, public administration is incapable of managing an efficient and integrated management to follow up the pace of urban growth. It was recognized three areas with different characteristics related to the waterfront of the neighborhoods: Reduto characterized as commercial, featuring an impressive index of institutional spaces, Campina, characterized as commercial use, with the highest rates of an unoccupied spaces, with an order space in the marginal area that provides free access to the population, and Cidade Velha, characterized as residential use, commercial activity also present and expressive in this space, where are found the largest number of conflicts on the waterfront of the studied area, the first two considered waterfront of consolidated urbanization and the latter as waterfront of sprawl. Through the questionnaires was possible to evaluate the basic formulation of indicators to be used in urban planning, as assessed on issues such as sanitation, water and power, street lighting, town planning and habitation, reflecting the popular assessment on the impact of application public policies on the waterfront of the central zone of Belém also identified himself as the subjective aspects of people's relationship with the river. It is noticed that despite some gaps in the UMP is well structured and focused on maintaining the social function of the city, but is necessary a critique of urban development model adopted, which is based on different theories and applications of the local reality, not taking into account social, historical and cultural contexts of the area in question. Despite almost twenty years of the UMP establishment, still has flaws and cannot be regarded as public policy which covers all aspects in spatial planning on the waterfront of the central zone of Belém. The proposal of a documentary is a way of trying to outsource the research results, through a language accessible and easily accepted by society in general.